Robust scareware image detection - Seifert, Christian; Stokes, Jay; Colcernian, Christina; Platt, John; Lu, Long (2013 International Conference on Acoustics, Speech, and Signal Processing, 2013)
In this paper, we propose an image-based detection method to identify web-based scareware attacks that is robust to evasion techniques. We evaluate the method on a large-scale data set that resulted in an equal error rate of 0.018%. Conceptually, false positives may occur when a visual element, such as a red shield, is embedded in a benign page. We suggest including additional orthogonal features or employing graders to mitigate this risk. A novel visualization technique is presented demonstrating the acquired classifier knowledge on a classified screenshot.